Still have math questions?

Ask our expert tutors
Algebra
Question

If \( v = m ^ { ( 6 - \frac { n } { r } ) } , \) ...

 If \( v = m ^ { ( 6 - \frac { n } { r } ) } , \) express \( n \) in terms of \( r , m \) and \( v \) by taking logarithms to base \( 10 . \) 

\( n = \frac { r } { \log m } ( 6 - \log v ) \) 

\( n = r \log m ( \log v - 6 \log m ) \) 

\( n = r ( 6 - \frac { \log v } { \log m } ) \) 

\( n = \frac { 1 } { m } ( 6 m r - r v )\) 

Answer

solve for \( n , v = m ( 6 - \frac { n } { r } ) : n = - \frac { r \ln ( v ) - 6 r \ln ( m ) } { \ln ( m ) }\) 

 

Solution
View full explanation on CameraMath App.